Recent Advances in Cellulose-Based Materials: Synthesis, Characterization, and Their Applications - Zhang, X.M.; Ma, M.G.; Yang, J.; Xiang, Z.; Zhu, J.F.; Alias, Y. (Hindawi Publishing Corporation, 2016)
Recently, sustainable energy sources and environmental problems have received more attention. As one of the most abundant polysaccharides and renewable resources on the earth, cellulose is widely used in environmental protection, water treatment, biomedical, and other fields owing to its particular characteristics such as mechanical properties, biodegradation, biocompatibility, and low toxicity. More importantly, cellulose could be used as an important resource for the transform to high value-added bioethanol, biomaterials, and biochemicals. Based on its wide applications and excellent properties, this special issue focused on the synthesis and applications of cellulose-based materials and explores the new synthetic methods, characterization analysis techniques, and high value-added applications fields of cellulose materials.